TRAFFICKING IN HUMAN BEINGS: PARADIGMS OF A SUCCESSFUL REINTEGRATION INTO SOCIETY (ALBANIAN CASE) - Muco, Ervin (European Scientific Journal, ESJ, 2013)
﻿Protection of human rights and reintegration of trafficked people is central to efforts made by governments around the globe aiming to prevent, combat, protect, assist, provide, and reintegrate victims of trafficking in social life. European Union and the United States represent main stakeholders against trafficking in human beings. In cooperation with the Council of Europe, the EU supports judicial reform, border control, customs management, improving the capacity of police to defeat organized crime and terrorism as well as simultaneously developing the capacity and institutions for the rehabilitation and reintegration of trafficking victims. Albania has also signed and ratified international conventions and has made changes to the criminalization of human trafficking in the national criminal legislation. A special focus is shown in the social services in the rehabilitation and reintegration of victims of trafficking. Palermo Protocol29 emphasizes two important elements in relation to human trafficking. First he states the effective prevention of trafficking through prosecution of traffickers and secondly protection of human rights and victim assistance to ensure their rehabilitation and reintegration into society. Reintegration refers to the process of recovery and socio-economic inclusion of individuals after a trafficking experience. Reintegration involves putting in a safe environment, access to a reasonable standard of living, opportunities for personal and economic development, and access to social and emotional support.